Prevalence and Distribution of Nonsyndromic Dental Anomalies in Children in Eastern Saudi Arabia: A Radiographic Study - Eman A. Bakhurji; Fatima Aldossary; Jood Aljarbo; Fatimah AlMuhammadi; Maysaa Alghamdi; Muhammad Ashraf Nazir (The Scientific World Journal)
Objectives. To report the prevalence and distribution of nonsyndromic dental anomalies in children in eastern Saudi Arabia. Methods. This retrospective records review study involved radiographic examination of 6–18 years old pediatric patients who attended the Dental Hospital of the College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia. Four calibrated examiners recorded nonsyndromic dental anomalies from patients’ digital orthopantomograms (OPG). The anomalies recorded were related to tooth number, shape, and location. Descriptive statistics, chi-square test, and Fisher exact tests were used to report prevalence and differences by gender, nationality, and medical history at the 5% significance level. Results. Of 2226 reviewed patients’ records, 1897 met the inclusion criteria and were included in the study. The study sample had equal distribution of males (52.6%) and females (47.4%) and comprised 81.2% Saudi children with a mean age of 8.8 ± 1.84 years. Most study subjects (97.8%) were in mixed dentition and 88.7% were healthy. The prevalence of dental anomalies was as follows: teeth rotations (24.5%), ectopically erupted teeth (6%), congenitally missing permanent teeth (5.4%), peg lateral (1.1%), supernumerary (0.5%), gemination (0.3%), and fusion (0.1%). No statistically significant differences were found in the distribution of dental anomalies by patients’ gender, medical history, and nationality (p value ≥0.05). Conclusion. This study showed that teeth rotations were the most common dental anomalies followed by ectopic eruptions and congenitally missing teeth. The study findings may guide dental practitioners to better diagnose and manage children with dental anomalies in eastern Saudi Arabia.